Analisis Keterampilan Bertanya Peserta Didik Kelas V SDN 101835 Bingkawan pada Pembelajaran IPA - Bukit, Servista; Kaban, Nomi Sari Br; Ramadhani, Rini; Bukit, Emi Br; Laratmase, Antonia Junianty; Rais, Rinovian; Haddar, Gamar Al (Civiliza Publishing, Indonesia., 2023)
Questioning skills is a skill that needs to be mastered by students at the elementary school level. Asking skills will encourage students to think in learning. Through asking questions can help students to master the concepts and facts in science learning. The focus of this research is to map students' questioning skills in science learning for heat material. The mapping of students' questioning skills is a form of analysis which is a form of preliminary study. The results of the analysis obtained 19 students who were less skilled in asking questions, 4 students who were quite skilled in asking questions, and 2 students who were skilled in asking questions. Thus, the teacher's efforts are still needed to facilitate students' questioning skills, for example by using the inquiry approach and contextual approach, applying the snowball throwing learning model and the debate learning model. The results of this study become an analysis of students' learning readiness for teachers to design learning according to children's learning styles.